ANALISIS FEKUNDITAS DAN DIAMETER TELUR KERANG DARAH (ANADARA ANTIQUATA) DI PERAIRAN PULAU AUKI, KEPULAUAN PADAIDO, BIAK, PAPUA - Widyastuti, Andriani (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTAnalysis of fecundity and egg diameter of cockles (Anadara antiquata) in Auki Island Water,Padaido Islands, Biak, Papua. This research was carried out to analyzes fecundity and eggdiameter of cockles (A. antiquata) in sandy base and seagrass bed in Auki island water, PadaidoIslands, Biak, Papua This research was conducted over 10 months (June 2009-March 2010).Samples were collected at monthly intervals and were measured the shell length and bodyweight. The colour of the gonad was used to determine the sex. Fecundity was calculated usingthe volumetric method with Sedwigck Rafter counting cell (SRC cell). The sex ratio was 1,00 :1,92 for cockles in sandy base and 1,00:1,67 for cockles in seagrass bed. Fecundity rangedbetween 100.068 - 4.288.312 for 51.70 to 70.80 mm in shell length for cockles in sandy base andranged between 134.025-3.127.500 for 41,20-66,80 mm in shell length for cockles in seagrassbed. Egg diameter ranged between 20-64 ?m for cockles in sandy base and ranged 10-64 ?m forcockles in seagrass bed.Key words: Cockles, Anadara antiquata, fecundity, egg diameter.